Venom-derived peptides for breaking through the glass ceiling of drug development - Freuville, Lou; Matthys, Chloé; Quinton, Loïc; Gillet, Jean-Pierre (Frontiers in Chemistry, 2024)
Venoms are complex mixtures produced by animals and consist of hundreds of components including small molecules, peptides, and enzymes selected for effectiveness and efficacy over millions of years of evolution. With the development of venomics, which combines genomics, transcriptomics, and proteomics to study animal venoms and their effects deeply, researchers have identified molecules that selectively and effectively act against membrane targets, such as ion channels and G protein-coupled receptors. Due to their remarkable physico-chemical properties, these molecules represent a credible source of new lead compounds. Today, not less than 11 approved venom-derived drugs are on the market. In this review, we aimed to highlight the advances in the use of venom peptides in the treatment of diseases such as neurological disorders, cardiovascular diseases, or cancer. We report on the origin and activity of the peptides already approved and provide a comprehensive overview of those still in development.